Агроекологічна модель формування якості врожаю винограду - Ляшенко, Г. В.; Соборова, О. М.; Ляшенко, В. О. (Київський національний університет імені Тараса Шевченка, 2016)
Аналізується стан проблеми моделювання формування якості врожаю сільськогосподарських культур з врахуванням агроекологічних умов. Виконується характеристика показників якості врожаю винограду. Обґрунтовується структура і параметри агроекологічної моделі формування якості врожаю винограду. Описуються блоки вхідної інформації і розрахункової агроекологічної інформації, блок розрахунку продуктивності винограду з акцентом на блоці якості врожаю. Здійснюється перевірка адекватності моделі з використанням результатів лабораторно польових досліджень, проведених у 2014 і 2015 роках на ділянках відділу ампелографії і клонової селекції ННЦ «ІВіВ ім. В.Є.Таїрова» з виноградом сортів середніх, середньопізніх і пізніх строків стиглості.

The state of a crop quality formation modeling problem based on agro-ecological conditions is analyzing. A characteristic of grapes crop quality indicators is performing: sugar in grapes and the value tytruyemoyi acidity. A structure and the parameters of an agroecological model of a grapes crop quality formation are grounded: sugar in grapes, the value tytruyemoyi a aciditya sunshine duration SS, the amount of average twenty-four hours (ΣTav>10°C), average day (ΣTdn>10°C) and night (ΣTn>10°C) air temperatures, and the difference between the daytime and nighttime temperatures (ΣTdn-ΣTn)>10°C as the most appropriate index of the daily temperatures rhythm during a growing season are proposed to use as these indexes. A block of ___ISSN 0868-6939 Фізична географія та геоморфологія. - 2016. - Вип. 2(82) input data and agroecological calculated information, a block of grape productivity calculation with an emphasis on a block of a crop quality are described. An examination of this model adequacy using the results of laboratory and field studies carried out in 2014-2015 in the areas of an ampelography and clonal selection department of NSC of "IWW named after V.E.Tairov " with grapes of medium, later than average and late ripening is carrying out.
Agroecological model of grapes crop quality
Keywords: агроекологічні умови; агроекологічна модель; виноград; строки стиглості; показники якості врожаю; структура і параметри моделі; адекватність моделі; agro-ecological conditions; agroecological model; grapes; ripening; crop quality indicators; a structure and parameters of the model; a model adequacy